Hambatan Pembelajaran Agama Hindu Terhadap Siswa Tuna Netra di Panti Mahatmia - I Wayan Titra Gunawijaya; Ni Ketut Tri Srilaksmi (Cetta: Jurnal Ilmu Pendidikan, 2020)
Education is the most important thing controlled by humans from generation to generation. Without education it will break the blindness of knowing the universe. Education will not recognize people with disabilities or the normal, the fulcrum is the will to learn. This has become the spirit of the students in Mahatmia orphanage to always study knowledge, including knowledge about the teachings of Hinduism. Surely there will be obstacles in the implementation of Education carried out at the Mahatmia Orphanage. The approach used in this study is a qualitative approach with the type of qualitative research sourced from primary data, namely members of the Mahatmia orphanage and Hindu religious teaching staff, while Primary data sources are related books and articles. To make it easier for researchers to obtain data, interview and literature data collection methods are used which are then analyzed and presented in the form of qualitative descriptions. The results of the study can be classified into two things: 1) The obstacles of learners who are blind people will naturally experience limitations in understanding the material presented. 2) the obstacle of the teaching staff is of course adjusting the learning methods applied so as to provide a correct understanding to the blind people at the Mahatmia Orphanage properly about the teachings of Hinduism. Through these obstacles, of course, the learning method becomes the main key in improving future learning so that religious learning, especially Hinduism, can be carried out effectively.